2017
DOI: 10.1063/1.4999094
|View full text |Cite
|
Sign up to set email alerts
|

Chip-scale white flip-chip light-emitting diode containing indium phosphide/zinc selenide quantum dots

Abstract: A method for preparing a quantum dot (QD)-white light-emitting diode (WLED) is reported. Holes were etched in the SiO2 layer deposited on the sapphire substrate of the flip-chip LED by inductively coupled plasma, and these holes were then filled with QDs. An ultraviolet-curable resin was then spin-coated on top of the QD-containing SiO2 layer, and the resin was cured to act as a protecting layer. The reflective sidewall structure minimized sidelight leakage. The fabrication of the QD-WLED is simple in preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The excellent color distribution uniformity was attributed to the reflective sidewall (side silicone resin) of the CSP, which reduced the amount of the side-emitted light (blue-ring effect). 22,23 These results indicated that the CSP may have a potential in illumination applications that require high color uniformity.…”
Section: Resultsmentioning
confidence: 89%
“…The excellent color distribution uniformity was attributed to the reflective sidewall (side silicone resin) of the CSP, which reduced the amount of the side-emitted light (blue-ring effect). 22,23 These results indicated that the CSP may have a potential in illumination applications that require high color uniformity.…”
Section: Resultsmentioning
confidence: 89%
“…However, in actual manufacturing, white LED is generally realized by blue LED chips and yellow phosphor [4] . The white light obtained from backlight structure realized in this way is missing in the red light band and has a low color gamut range [5] . Another method to create white light is to combine a blue chip with two other types of QDs, red and green [6] .…”
Section: Introductionmentioning
confidence: 99%